Ganji Formulation for Patients with Hepatocellular Carcinoma Who Have Undergone Surgery: A Multicenter, Randomized, Double-Blind, Controlled Trial. (19th June 2019) - Zhang, Jing-Hao; Zheng, Chao; Zhu, Xiao-Jun; Zhang, Xin; Hou, Zhi-Jun; Zhou, Zhen-Hua; Wang, Yu-Qing; Wang, Kai-Xia; Yu, Zhuo; Li, Man; Gao, Yue-Qiu; Sun, Xue-Hua
Abstract : Objective. To ascertain the efficacy and safety of Ganji Formulation (GF) for patients with Hepatocellular carcinoma (HCC) who had undergone surgery. Materials and Methods. A total of 262 HCC patients who had undergone liver resection, local ablation, or transcatheter arterial chemoembolization (TACE) were divided randomly into the treatment group and control group. The former was treated with GF and the later with placebo, both for 6 months. The primary endpoint was overall survival (OS). Second endpoints were disease-free survival (DFS) or time to disease progression (TTP). Results. OS of the treatment group was significantly longer than that of the control group ( P < 0.05). Subgroup analysis showed that, for patients who received TACE, the TTP was significantly longer in the treatment group than in the control group (P < 0.05). However, for patients who underwent liver resection or local ablation, there was no significant difference in DFS between the two groups ( P > 0.05). Conclusion. GF could improve postoperative cumulative survival and prolong the TTP. This clinical trial number is registered withChiCTR-IOR-15007349 .